Oscillatory behavior of a fifth-order differential equation with unbounded neutral coefficients - GRAEF, John R.; AVCI, Hakan; ÖZDEMIR, Osman; TUNÇ, Ercan (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
The authors study the oscillatory behavior of solutions to a class of fifth-order differential equations with unbounded neutral coefficients. The results are obtained by a comparison with first-order delay differential equations whose oscillatory characters are known. Two examples illustrating the results are provided, one of which is applied to Euler type equations. Mathematics Subject Classification (2010): 34C10, 34K11, 34K40 Received 25 September 2020; Accepted 19 January 2021. Published Online: 2023-12-11 Published Print: 2023-12-30